Improving visual-spatial ability through anatomy apron in respiratory system learning - Tasya Khaeratunnisa; Arda Arda; Siti Rabiatul Adawiyah (STKIP Persada Khatulistiwa Sintang, 2026)
This study was undertaken to address the ongoing challenges students encounter in comprehending abstract anatomical ideas, especially those necessitating robust visual-spatial abilities, attributed to the inadequate utilization of tangible learning resources in science classes. This study investigates the impact of anatomical teaching aids on the visual-spatial abilities of eighth-grade students studying the human respiratory system at MTs Negeri 3 Palu. A quasi-experimental approach utilizing a pretest-posttest control group was implemented. The sample comprised 36 students, allocated into an experimental group of 18 students and a control group of 18 students. The experimental group utilized an anatomical apron as a teaching tool, whereas the control group was instructed by conventional memorizing techniques. A validated 15-item assessment was employed to evaluate pupils' visual-spatial abilities. Data were investigated utilizing N-Gain computations and an independent samples t-test subsequent to the fulfillment of normality and homogeneity assumptions. The findings indicated that the experimental group's average N-Gain score was classified as high and surpassed that of the control group. The t-test analysis produced a significance (2-tailed) value of 0.000 (< 0.05), signifying the rejection of H?. The findings indicate that anatomical apron teaching aids enhance students' visual-spatial abilities in the study of the human respiratory system.